2011
DOI: 10.1002/hlca.201000157
|View full text |Cite
|
Sign up to set email alerts
|

Cycloartane Glycosides from Three Species of Astragalus (Fabaceae)

Abstract: Nine cycloartane-type glycosides were isolated from three species of the genus Astragalus (Fabaceae): From the aerial parts of A. cicer L., two new saponins, cicerosides A and B (1 and 2, resp.), i.e., a tetradesmosidic and tridesmosidic cycloartane-type glycosides besides one known compound, from the roots of A. sempervirens Lam., one known saponin, and from the roots of A. ptilodes Boiss. var. cariensis Boiss., five known compounds. Their structures were established mainly by 600-MHz 2D-NMR techniques ( 1 H,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The 31 carbon resonances of the aglycone part consisted of 6 methyl carbons; 11 methylene carbons, 1 of which was oxygenated; 8 methine carbons, 3 of which bore oxygen functionalities; and 7 quaternary carbons comprising 1 carbonyl and an oxygenated carbon. Both the 1 H upfield methylenic protons at δ H 0.36 and 0.56 (each 1H, doublet with J = 4.0 Hz) and the six unsaturation degrees of the aglycone moiety led to define a carboxylic-acid-substituted cycloartane scaffold [12,13] (Figure 1 and Supplementary Materials). The thorough analysis of the COSY, HSQC, and HMBC spectra led to fully assign the 1 H and 13 C signals for compound 1 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 31 carbon resonances of the aglycone part consisted of 6 methyl carbons; 11 methylene carbons, 1 of which was oxygenated; 8 methine carbons, 3 of which bore oxygen functionalities; and 7 quaternary carbons comprising 1 carbonyl and an oxygenated carbon. Both the 1 H upfield methylenic protons at δ H 0.36 and 0.56 (each 1H, doublet with J = 4.0 Hz) and the six unsaturation degrees of the aglycone moiety led to define a carboxylic-acid-substituted cycloartane scaffold [12,13] (Figure 1 and Supplementary Materials). The thorough analysis of the COSY, HSQC, and HMBC spectra led to fully assign the 1 H and 13 C signals for compound 1 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The plants of Astragalus genus have been proved to be the richest source of cycloartane-type saponins, possessing cardiotonic, hypocholesteremic, anti-depressive and antiblastic actions as well as immunomodulatory activity [7]. This promising spectrum of pharmacological effects led researchers to further search for structurally interesting cycloartane glycosides from the genus.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Commonly, the aglycon of cycloartane-type saponins such as 1 – 62 possess an acyclic side chain at the 17-position. For the 17-acyclic side chain substituted cycloartane-type saponins, obtained from the Astragalus genus, the 24-position is often replaced by oxygen containing groups, and there are two kinds of steric configuration constituents with 24 S ( 1 – 28 ) [6,9,10,11,12,13,14,15,16,17,18,19,20,21,22] or 24 R ( 29 – 48 ) [7,14,15,16,17,23,24,25,26,27,28,29,30,31,32,33,34].…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Others are a source of the economically important natural product, gum tragacanth. It is reported that some of Astragalus plants are well-known for their hepatoprotective, antiviral and immunostimulant activities [8]. Previous reports showed Astragalus plants to be a great source of saponins, flavonoids, and polysaccharides [9].…”
Section: Introductionmentioning
confidence: 99%